Formative research for the development of baby water, sanitation, and hygiene interventions for young children in the Democratic Republic of the Congo (REDUCE program) - Jennifer Kuhl; Lucien Bisimwa; Elizabeth D. Thomas; Camille Williams; Joseph Ntakirutimana; Nicole Coglianese; Sarah Bauler; Ruthly François; Presence Sanvura; Jean Claude Bisimwa; Patrick Mirindi; Christine Marie George (BMC, 2021)
Abstract Background Research exploring the unique exposure pathways to fecal pathogens for young children and innovative water, sanitation, and hygiene (WASH) interventions for susceptible pediatric populations is needed to reduce the burden of diarrheal diseases and stunting globally. The Reducing Enteropathy, Diarrhea, Undernutrition, and Contamination in the Environment (REDUCE) program seeks to 1) identify exposure pathways to fecal pathogens that are significant contributors to morbidity for young children in South Kivu, Democratic Republic of the Congo, and 2) develop and evaluate scalable interventions that reduce fecal contamination and exposure from these pathways. The formative research portion of the project sought to identify feasible and acceptable WASH interventions to modify behaviors found to be associated with diarrheal disease and impaired growth in our REDUCE cohort study. Methods Ninety-one semi-structured interviews, 6 focus group discussions, and a pilot study of 102 households were conducted during 24 months of formative research. Thirty-one interviews and six focus group discussions were conducted with caregivers, community health workers, and village leaders to explore existing WASH practices and to identify barriers and facilitators to WASH behaviors. Findings were organized using the Integrated Behavioral Model for Water, Sanitation and Hygiene to facilitate interpretation and identify determinants to Baby WASH behaviors in this setting. Care Group modules and enabling technology were developed based on exploratory findings and then revised during a two-part, iterative pilot study. Sixty interviews were conducted with participants in a pilot study of the REDUCE Baby WASH Care Group modules to learn about their experiences with the intervention. Results Six REDUCE Baby WASH Care Group modules were developed based on formative research findings and covered the following topics: 1) living with animals; 2) child mouthing of fomites and feces; 3) composting animal feces; 4) child feces disposal; 5) handwashing with soap; and 6) water treatment. Conclusion This study took a theory-driven and evidence-based approach to formative research and the development of the REDUCE Baby WASH Care Group modules. Intervention design focused on interrupting the exposure routes for infants and young children to fecal pathogens in the environment and promoting low-cost, low-burden Baby WASH behavioral recommendations and enabling technology. These developed REDUCE Baby WASH Care Group modules are currently being rolled out to over 1,000,000 beneficiaries in Democratic Republic of the Congo.